PENGARUH PENGGUNAAN METODE MEMBACA SURVEI, QUESTION, READ, RECITE, AND REVIEW (SQ3R) DENGAN MINAT BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA (Studi Eksperimen pada Siswa Kelas V SDN Jati Warna IV Kabupaten Bekasi) - Nina Yuminar Priyanti (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2019)
The aims of this thesis to examine 1) differences in Indonesian language score between SQ3R reading method and the method of reading Layap (Skimming). 2) the interaction between the learning method and the reading interest with Indonesian Language score. 3) differences of Indonesian language score between SQ3R reading method and the reading Layap (Skimming) method on the students who have a high reading interest. 4) differences in Indonesian language score between SQ3R reading method and the reading Layap (Skimming) method on the students who have a low reading interest.This research used experimental research. The population was the class V SDN Jati Warna IV Pondok Melati Bekasi City. Sample in this study used purposive sampling, the sample is taken accordancelly with the sample requirements as much as needed. Class B is the control class that used Skimming reading method and class C is the treatment class that used SQ3R reading method. Class B and class C used as research subjects because these two classes have the same characteristics of respondents. The data instrument of Indonesia language score variable (Y) used the test items and reading interest (X) used a test Questionnaire / questioner student interest. Validity is calculated by using SPSS version 17 and reliability by using Cronbach's Alpha. Method of processing or analysis of the data is used descriptive analysis and inferential analysis. Descriptive analysis was presented by form of data to the list of frequency distribution and histogram, the mean (average), median (middle data), mode (mode), standard deviation, minimum (lowest score), maximum (highest score). The data will be analyzed with ANOVA 2 x 2 method and Turkey test. However, to test the hypothesis it has been done the prerequisite test, which was the Kolmogorov- Smirnov normality and homogeneity test and Levene's test with calculations using SPSS 17. Results of statistical test showed that data was normal and homogeneous.The results showed 1) There are differences in Indonesian language score between SQ3R reading method and the method of reading Layap (Skimming). 2) There are interaction between the learning method and the reading interest with Indonesian Language score. 3) There is no difference of average Indonesian language score between SQ3R reading method and the method of reading Layap (Skimming) on the students who have a high reading interest. 4) There are differences of average Indonesian language score between SQ3R reading method and the method of reading Layap (Skimming) on the students who have a low reading interest.